The effects of musical fit on consumers’ choice when opportunity and ability is limited - Yeoh, Joanne Pei Sze; North, Adrian (Universiti Putra Malaysia Press, 2013)
Two experiments were carried out to investigate the impacts of musical ‘fit’ on the choice between two products when the opportunity and ability to consider their relative advantages were either limited (Experiment 1) or ample (Experiment 2). Experiment 1 asked participants to read complex descriptions of two watches within a short time. The watches corresponded with either the luxurious stereotype of classical music or the modish stereotype of funk music. The participants chose between them while listening to either classical music, funk music or no music. Experiment 2 repeated the methodology except that the alternative choice scenario gave the participants more time to choose between the watches. In Experiment 1, when classical music was played, more participants chose the ‘luxurious’ watch and, when funk was played, more participants chose the modish watch. In Experiment 2, choices were not influenced by the music. This suggests that musical ‘fit’ influences the preferences between products, but only when opportunity and ability to consider them are limited.